Molecular Evidence for Multiple Origins of the European Spined Loaches (Teleostei, Cobitidae) - Perdices, Anabel; Bohlen, Joerg; Šlechtová, Vendula; Doadrio, Ignacio (PloS one, 2016)
We present a phylogenetic investigation of the Northern Clade, the major monophyletic clade within the freshwater fish family Cobitidae, one of the most prominent families of freshwater fishes found in Asian and European waters. Phylogenetic reconstructions based on the cytochrome b and RAG-1 genes show the genera Microcobitis, Sabanejewia, Koreocobitis and Kichulchoia as monophyletic groups. These reconstructions also show a Cobitis sensu lato and a Misgurnus sensu lato group. The Cobitis sensu lato group includes all species of Cobitis, Iksookimia, Niwaella and Kichulchoia, while the Misgurnus sensu lato group includes Misgurnus, Paramisgurnus and Koreocobitis. Although the monophyly of both the Cobitis sensu lato and Misgurnus sensu lato groups is supported, relationships within the groups are incongruent with current generic definitions. The absence of monophyly of most genera included in the Cobitis sensu lato group (Cobitis, Iksookimia and Niwaella) or their low genetic differentiation (Kichuchoia) supports their consideration as synonyms of Cobitis. Molecular phylogenies indicate that the Asian species of Misgurnus experienced a mitochondrial introgression from a lineage of Cobitis. We also find two nuclear haplotypes in the same Cobitis species from the Adriatic area that, in the absence of morphological differentiation, may indicate molecular introgression. Most lineages within the Northern Clade consist of species found in East Asia. However, some lineages also contain species from Europe and Asia Minor. The phylogenetic relationships presented here are consistent with previous studies suggesting an East Asian origin of the Northern Clade. According to the current distributions and phylogenetic relationships of the Misgurnus sensu lato and Cobitis clade lineages, particularly of M. fossilis and C. melanoleuca, the range expansion of East Asian species into Europe was most likely via Siberia into Northern and Central Europe. Phylogenetic analyses also show that the Cobitis sensu lato group consists of two clear subgroups (I and II), each presenting geographical differences. Subgroup I is distributed exclusively in East Asian drainages with an Eastern European offshoot (C. melanoleuca), whereas Subgroup II includes species widespread throughout Europe (including the Mediterranean), Asia Minor, the Black Sea and the Caucasus, with some lineages related to species restricted to East Asia.
Keywords: Haplotypes; DNA, Mitochondrial; Sequence Homology, Nucleic Acid; Asie; Genetic Speciation; vznik druhů (genetika); Evolution, Molecular; Evropa; cytochromy b; geny RAG-1; haplotypy; Genes, RAG-1; fylogeneze; Asia; zvířata; mitochondriální DNA; sekvenční homologie nukleových kyselin; Animals; molekulární sekvence - údaje; Cypriniformes; Cytochromes b; Molecular Sequence Data; Europe; Phylogeny; molekulární evoluce; máloostní